Contragenic functions on spheroidal domains. (13th March 2018) - García‐Ancona, Raybel; Morais, Joao; Porter, R. Michael
Abstract : We construct bases of polynomials for the spaces of square‐integrable harmonic functions that are orthogonal to the monogenic and antimonogenic R 3 ‐valued functions defined in a prolate or oblate spheroid.